ECONOMIC AGENCY OF MUSLIM WOMEN IN THE ERA OF GLOBALIZATION - Dinda Aprilia; Desi Mardina; Khairani Hayat Situmorang (CV. Barokah Publsiher, 2026)
This study examines the economic agency of Muslim women in the era of globalization, focusing on their participation in economic activities, the factors influencing their involvement, and the impact of globalization on their empowerment. The research employs a qualitative approach using a literature-based method, drawing on secondary data from academic journals, books, and reports from international organizations. The findings indicate that Muslim women’s economic agency has significantly increased, particularly in entrepreneurship, formal employment, and the digital economy. This development reflects their growing ability to make independent economic decisions and access resources, as emphasized in the capability approach of Amartya Sen. However, their participation is influenced by both supporting factors, such as education, technological advancement, and institutional support, and inhibiting factors, including socio-cultural norms, limited access to capital, and structural inequalities, as highlighted by Naila Kabeer. Furthermore, globalization plays a dual role by providing broader economic opportunities while also reproducing certain inequalities, as argued by Saskia Sassen. In conclusion, although globalization has enhanced the economic agency of Muslim women, comprehensive efforts are still needed to address existing barriers and ensure inclusive and sustainable economic empowerment.